Gene expression changes in the brain of a Cushing's syndrome mouse model. (1st April 2022) - Amaya, Jorge Miguel; Viho, Eva M. G.; Sips, Hetty C. M.; Lalai, Reshma A.; Sahut‐Barnola, Isabelle; Dumontet, Typhanie; Montanier, Nathanaëlle; Pereira, Alberto M.; Martinez, Antoine; Meijer, Onno C.
Abstract: Excess glucocorticoid exposure affects emotional and cognitive brain functions. The extreme form, Cushing's syndrome, is adequately modelled in the AdKO2.0 mouse, consequential to adrenocortical hypertrophy and hypercorticosteronemia. We previously reported that the AdKO2.0 mouse brain undergoes volumetric changes that resemble closely those of Cushing's syndrome human patients, as well as changes in expression of glial related marker proteins. In the present work, the expression of genes related to glial and neuronal cell populations and functions was assessed in regions of the anterior brain, hippocampus, amygdala and hypothalamus. Glucocorticoid target genes were consistently regulated, including CRH mRNA suppression in the hypothalamus and induction in amygdala and hippocampus, even if glucocorticoid receptor protein was downregulated. Expression of glial genes was also affected in the AdKO2.0 mouse brain, indicating a different activation status in glial cells. Generic markers for neuronal cell populations, and cellular integrity were only slightly affected. Our findings highlight the vulnerability of glial cell populations to chronic high levels of circulating glucocorticoids. Abstract :